Communicative strategies and their influence on the speaking skill in students of sixth grade EGB at Unidad Educativa Particular Suiza, school year 2019-2020 - Colcha Colcha, Rosa Marlene (2020)
The communication strategies are understood as those that allow developing the skills that are required, in the case of the English language, these allow to improve the speech of said language, making it more didactic by changing the traditional strategies that are usually applied in the classrooms, modifying them for those who have a higher degree of motivation in students. Communication strategies can be used by a student or a native speaker of a foreign language to achieve a specific communicative objective, despite sufficient knowledge of the language, these strategies can also be seen as mechanisms used to solve communication problems. In the development of oral speech, the expression plays an important role, given the set of methods that determine the general guidelines that must be followed for effective oral communication, that is, to express thoughts without obstacles in this way. Since it is used daily, most people do not attribute to the language the meaning it has in all its aspects, therefore, it is often used incorrectly. Sometimes the ignorance of strategies and the non-application of them do not allow us to constantly improve through systematic, focused and conscious practice............